Urban Imagery in the Old English Exodus and its Hermeneutics - Olesiejko, Jacek (Studia Anglica Posnaniensia, 2022)
The present article offers a critical reading of the Old English Exodus, a poem that is an Old English versified adaptation of an episode from the biblical story of Exodus that narrates Israelites’ passage across the Red Sea and the destruction of Pharaoh’s army. The aim of this article is to analyse the poem’s urban and exilic imagery that strongly relies on the metaphorical representation of the Israelites as a city, as they are actually in exile and on the way to Canaan, and of the metaphorical representation of the walls of the Red Sea as the walls of a hall that is destroyed along with the Egyptian army. The argument of the present article is that in Exodus the poet uses the imagery of a hall and exile, derived from heroic and secular verse, as a hermeneutic key to read the biblical exodus typologically, tropologically, and anagogically. The metaphor of the key that opens the Scripture, which the poet uses in Exodus, encourages the reader to unveil the hidden meaning of the narrative. The poet inverts the conventional imagery of the hall and exile in the poem to emphasise narrative moments that require the reader to explore the letter of the poem for additional layers or signification.